Understanding agroecology and its synergy with national park management: a case study in Wuyishan of China - Siyuan He; Bojie Wang (Sustainable Futures, 2025)
Despite the growing recognition of agroecology as a promising approach to sustain agriculture while conserving biodiversity, the factors that hinder or facilitate its adoption remain poorly understood. This study explores the mechanisms underlying tea farmers’ agroecological practices within the Wuyishan National Park, employing a grounded theory approach. We synthesised a conceptual model that elucidates the juxtaposition of traditional and modern practices, as well as farmers’ common but differentiated aspirations for development. Our findings highlight the importance of integrating traditional knowledge with modern innovations and providing tailored support to harness the multiple values of agrosystems. This approach fosters a synergistic relationship between agricultural sustainability and biodiversity conservation, offering insights for sustainable park management and agroecological transitions.